(untitled) (Revista Electrónica REDINE, 2018)
This work is an epistemological research which by way of inquiry in qualified documentary sources and handling categories necessary with the philosophy of knowledge has made confrontations between models of reason in the face of addressing the issue of the complexity that involves both social and professional relationships of graduates the DACE/UCLA. A model of reason (logic) tries to interpret and explain the reality guiding thinking in plan to interpret it. The interest of this work are the typical processes of social organizations whose complexity warrants an approach pensamental beyond linear thinking based on the analytic logic and understanding of reality as a totality. From there the need to supplement the curriculum of races offering the DACE in topics that have to do with these logics currently absent in his Pensa of study, as well as also the General system theory as a theoretical frame of reference for social organizations. "Therefore, proposes an instructional program that contemplates such issues, they are: "Analytical logic and laws of appoggiatura "," dialectical logic and the Ontoguiaturas", "Fuzzy logic and its reasoning theoretical", "The General theory of systems" and “Logics and applied systems”.